Diálogo entre Cortes: um estudo sobre a aplicabilidade da Convenção Americana sobre Direitos Humanos em litígios minerários do Tribunal de Justiça do Pará - ALVES, Sandro Júnior do Carmo (Universidade Federal do Pará, 2025)
The general objective of this Master's Dissertation is to describe, based on jurimetric data and the analysis of judgments, how the rights protected by the American Convention on Human Rights (ACHR) and its related jurisprudence can serve as pro homine instruments in the dialogue between the Tribunal de Justiça do Pará (TJ-PA) and the Inter-American Court of Human Rights (IACHR) in cases involving the mining industry in the state of Pará. A descriptive research with an inductive method was used to analyze the judgments. The bibliographic review revealed that environmental conflicts related to mining are associated with the intrinsic dimensions of this model of exploration, which causes negative impacts both on the environment and on the quality of life of local communities. For the purposes of analysis of the Dissertation, these conflicts were categorized into 7 types. As a theoretical framework, the research adopted the theory of “dialogue between Courts”, which explores communication between different jurisdictions for a broad defense of human rights. Given that Brazil is a signatory to the ACHR and is under the jurisdiction of the Inter-American Court of Human Rights, the State must respect the rights enshrined in this Convention, in its related case law, and in other documents, such as Advisory Opinion No. 23 of 2017, which establishes the relationship between the environment and human rights. The analysis of the 187 rulings of the TJ-PA revealed that 129 refer to agrarian conflicts, followed by those related to the progressive development of society. The company Vale S.A. is the largest litigant, present in 120 rulings. Regarding the grounds used, procedural law rules stood out, cited 211 times, followed by agrarian law rules, mentioned 82 times. The most recurrent case law was of a civil procedural nature, followed by agrarian law, while the doctrinal references were also predominantly procedural, followed by civil law. It was observed that the ACHR could be applied in all rulings. It was also found that arguments related to economic rights and property rights of mining companies still prevail over the rights to quality of life of local communities. Even when decisions are favorable to residents, these rights are not interpreted comprehensively, as has already been done by the case law of the Inter-American Court of Human Rights. Thus, it is clear that there is a need for dialogue between the TJPA and the Inter-American Court of Human Rights so that court decisions related to mining and human rights do not exacerbate social inequalities.